Barriers to implementing advanced skills in trauma and emergency nurse specialist practice - Haroldene Stevens; Cornelle Young; Tshepo L. Motsepe; Tendani Mabuda (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: A postgraduate specialist programme in trauma and emergency nursing is offered to help address the high burden of injuries and emergencies in the South African healthcare system. The trauma and emergency nurse specialists’ advance skills and expertise have been associated with improved patient outcomes, yet they continue to face barriers that constrain the full scope of their practice.